King Alfred’s Castle: Or, How to Memorialise the Yorkshire Petition of 1769 - Cox, O (New Arcadian Press, 2013)
King Alfred’s Castle, constructed for the Yorkshire merchant Jeremiah Dixon in the summer of 1769, is an important example of the politicisation of the landscape in a contested decade. This is the first detailed study of the Gothic folly, which situates this mercantile intervention into landscape gardening within its provincial and national contexts.